New benthic mysids from the littoral waters of Kenya: Mysidopsis kenyana n.sp. and Nouvelia natalensis mombasae n.g., n.sp. - - Bacescu, M.; Vasilescu, E. (Rev. Roum. Biol., Zool., 1973)
M723
M723; NeMys doc_id: 97